The Burning of a Sector Police Office by the Community from a Criminological Perspective - Radhali Radhali; Wahyu Ramadhani (UNIFIKASI : Jurnal Ilmu Hukum, 2020)
This study aims to identify the legal analysis of the burning of a Sector Police Office by the community from a criminological perspective as well as to analyze the level of community trust in police after the burning of the Sector Police Office based on criminological theories. This descriptive-analytical study applied a normative juridical approach. The results of the legal analysis of the burning of a Sector Police Office by the community from a criminological perspective showed that, according to the anomic theory, the burning is due to the influence of social structure as a correlative factor in the burning of the Sector Police Office of Bendahara. This influence can be seen from the disparity between the goals to be achieved and the means used in achieving these goals. Hence, the community took steps to burn down the Sector Police Office to achieve its goals. Further, the level of community trust in police after the burning of the Sector Police Office was demonstrated through association theory, social control theory, and neutralization theory. Based on the description of the criminological theories and its relation to the phenomenon of the burning of the Sector Police Office of Bendahara, there needs to be an evaluation of the application of the law as the harmonization of the law in the context of criminal provisions is needed. Pembakaran Kepolisian Sektor oleh Masyarakat dalam Perspektif Kriminologi Tujuan penelitian ini yaitu untuk mengetahui analisis hukum terhadap pembakaran Kepolisian Sektor oleh masyarakat dalam perspektif kriminologi, untuk mengetahui kepercayaan masyarakat terhadap kepolisian pasca pembakaran Kepolisian Sektor menurut teori-teori kriminologi. Spesifikasi penelitian yang digunakan adalah penelitian bersifat deskriptif-analitis dengan pendekatan yuridis normatif. Hasil penelitian dari analisis hukum terhadap pembakaran Kepolisian Sektor oleh masyarakat dalam kriminologi bahwa menurut teori anomi menekankan pengaruh struktur sosial sebagai faktor korelatif terjadinya pembakaran Kepolisian Sektor Bendahara. Pengaruh ini terlihat dari adanya disparitas antara tujuan yang hendak dicapai dengan sarana yang digunakan dalam mencapai tujuan tersebut. Hal ini akhirnya mengambil langkah-langkah pembakaran Kepolisian Sektor Bendahara untuk mencapai tujuannya. Selanjutnya tingkat kepercayaan masyarakat terhadap kepolisian pasca pembakaran Kepolisian Sektor menunjukkan melalui teori asosiasi; teori kontrol social dan teori netralisasi. Berdasarkan uraian teori-teori kriminologi tersebut dihubungkan fenomena pembakaran Kepolisian Sektor Bendahara saat ini sangatlah dibutuhkan sebagai evaluasi terhadap penerapan hukum sehingga diperlukan harmonisasi hukum dalam konteks ketentuan pidana